2008
DOI: 10.1177/104063870802000204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of histologic techniques for the diagnosis of bovine tuberculosis in the framework of eradication programs

Abstract: Rapid diagnosis of tuberculosis in cattle reacting positive in antemortem assays is crucial in countries where eradication programs are operated to confirm the presence of the infection in tuberculosis-free herds. This study evaluated the accuracy of histopathologic examination by hematoxylin and eosin and Ziehl-Neelsen (ZN) staining applied in this framework, when suspected lesions are caused by low infectious doses and are detected in early stages of the disease. For this purpose, histologic methods were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
3
21
0
8
Order By: Relevance
“…There was good agreement between the histopathology findings, bacterial culture and identification (Rivera-Posada et al 2011a,b, present study), suggesting that histopathological examination is a reliable tool that allowed identification of typical vibriosis lesions and could contribute to the differentiation from other causes. Varello et al (2008) compared histologic techniques and bacteria cultures for the diagnosis of bovine tuberculosis reporting similar results.…”
Section: Discussionsupporting
confidence: 49%
“…There was good agreement between the histopathology findings, bacterial culture and identification (Rivera-Posada et al 2011a,b, present study), suggesting that histopathological examination is a reliable tool that allowed identification of typical vibriosis lesions and could contribute to the differentiation from other causes. Varello et al (2008) compared histologic techniques and bacteria cultures for the diagnosis of bovine tuberculosis reporting similar results.…”
Section: Discussionsupporting
confidence: 49%
“…VARELLO et al (2008) analyzed 173 suspected tissue samples from bovines and identified 117 of them (67.63%) as tuberculosis using Hematoxylin-eosin staining, but when Ziehl-Neelsen staining was used, AFB was identified in only 31 samples (17.91%). This data underlines the need to associate histopathological characterization and AFB identification, since the latter can be limited due to low quantity of bacteria in lesions.…”
Section: Discussionmentioning
confidence: 99%
“…An estimate of granuloma area in a lung section was determined by taking the average of approximately 5 microscopic (x100) ϐiel-ds examined in one plane of section. Despite been lung samples instead lymph nodes, samples were categorized according to Varello et al (2008), as follows: Positive: tubercular granuloma displaying central necrosis with or without mineralization surrounded by macrophages, lymphocytes, plasma cells, neutrophils, epithelioid cells, and Langerhan's giant cells, and enclosed partly or completely by a thin capsule. Inconclusive: lesion characterized by irregular with no capsulated clusters of epithelioid macrophages; associated with a not Langerhan's-type multinucleated giant cells and necrosis.…”
Section: Methodsmentioning
confidence: 99%